In vitro characterization of a novel Isu homologue from Drosophila melanogaster for de novo FeS-cluster formation. Issue 1 (14th October 2016) - Dzul, Stephen P.; Rocha, Agostinho G.; Rawat, Swati; Kandegedara, Ashoka; Kusowski, April; Pain, Jayashree; Murari, Anjaneyulu; Pain, Debkumar; Dancis, Andrew; Stemmler, Timothy L.
Abstract : Model for mitochondrial Fe–S cluster assembly with bypass mechanisms for FeS mineral accumulation. Abstract : FeS-clusters are utilized by numerous proteins within several biological pathways that are essential for life. In eukaryotes, the primary FeS-cluster production pathway is the mitochondrial iron–sulfur cluster (ISC) pathway. In Saccharomyces cerevisiae, de novo FeS-cluster formation is accomplished through coordinated assembly with the substrates iron and sulfur by the scaffold assembly protein "Isu1". Sulfur for cluster assembly is provided by cysteine desulfurase "Nfs1", a protein that works in union with its accessory protein "Isd11". Frataxin "Yfh1" helps direct cluster assembly by serving as a modulator of Nfs1 activity, by assisting in the delivery of sulfur and Fe(ii ) to Isu1, or more likely through a combination of these and other possible roles. In vitro studies on the yeast ISC machinery have been limited, however, due to the inherent instability of recombinant Isu1. Isu1 is a molecule prone to degradation and aggregation. To circumvent Isu1 instability, we have replaced yeast Isu1 with the fly ortholog to stabilize our in vitro ISC assembly system and assist us in elucidating molecular details of the yeast ISC pathway. Our laboratory previously observed that recombinant frataxin from Drosophila melanogaster has remarkable stability compared to the yeast ortholog. Here we provide the first characterization of D. melanogaster Isu1 (fIscU) and demonstrate its ability to function within the yeast ISC machinery both in vivo and in vitro . Recombinant fIscU has physical properties similar to that of yeast Isu1. It functions as a stable dimer with similar Fe(ii ) affinity and ability to form two 2Fe–2S clusters as the yeast dimer. The fIscU and yeast ISC proteins are compatible in vitro ; addition of Yfh1 to Nfs1–Isd11 increases the rate of FeS-cluster formation on fIscU to a similar extent observed with Isu1. Finally, fIscU expressed in mitochondria of a yeast strain lacking Isu1 (and its paralog Isu2) is able to completely reverse the deletion phenotypes. These results demonstrate fIscU can functionally replace yeast Isu1 and it can serve as a powerful tool for exploring molecular details within the yeast ISC pathway.